2021
DOI: 10.1186/s13018-021-02864-x
|View full text |Cite
|
Sign up to set email alerts
|

Severity and location of lumbar spine stenosis affects the outcome of total knee arthroplasty

Abstract: Background Recent studies have noted that patients with pre-existing lumbar spinal stenosis (LSS) have lower functional outcomes after total knee arthroplasty (TKA). Given that LSS manifests heterogeneously in location and severity, its influence on knee replacement merits a radiographically targeted analysis. We hypothesize that patients with more severe LSS will have diminished knee mobility before and after TKA. Methods This retrospective case … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…also found that by reducing the internal diameter of the spine, especially in lumbar levels 1–4, and creating pressure on the spinal cord, the range of motion of the lower limbs significantly decreased, and the pain and spasm of the lower limbs, including in the knees, were increased. [ 27 ] However, no significant relationship between spine diseases and pain was found in the patients of the present study. To explain the disparity between the results of the studies mentioned and those of the current study, it is possible to point to the type of previous studies, the lack of investigation into the age groups of patients and their gender in the current study, and the specific relationship between spinal disease (spondylolysis myelopathy) and pain in the previous studies.…”
Section: Discussioncontrasting
confidence: 68%
“…also found that by reducing the internal diameter of the spine, especially in lumbar levels 1–4, and creating pressure on the spinal cord, the range of motion of the lower limbs significantly decreased, and the pain and spasm of the lower limbs, including in the knees, were increased. [ 27 ] However, no significant relationship between spine diseases and pain was found in the patients of the present study. To explain the disparity between the results of the studies mentioned and those of the current study, it is possible to point to the type of previous studies, the lack of investigation into the age groups of patients and their gender in the current study, and the specific relationship between spinal disease (spondylolysis myelopathy) and pain in the previous studies.…”
Section: Discussioncontrasting
confidence: 68%
“…The authors have pointed out that undiagnosed diseases related to the spinal cord and spine may be the reason for the continuation or exacerbation of pain after TKA [23]. Shepard and colleagues also found that by reducing the internal diameter of the spine, especially in lumbar levels 1 to 4, and creating pressure on the spinal cord, the range of motion of the lower limbs signi cantly decreased, and the pain and spasm of the lower limbs, including in the knees, is increased [24]. However, no signi cant relationship between spine diseases and pain was found in the patients of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…All spinopelvic parameters were obtained in accordance to institutional protocol [29]. There were no statistical differences in materials used or post-operative radiographic parameters in accordance with prior studies from our group [29,30].…”
Section: Study Design and Spinal Alignment Measurementsmentioning
confidence: 99%
“…Studies have shown that spinal sagittal mismatch deformity and lumbar stenosis negatively affect TKA, but there is little evidence regarding spondylolisthesis affecting TKA outcomes [29][30]. Thus, we performed a retrospective review to analyze the relationship of predisposing spondylolisthesis and TKA outcomes among patients receiving TKAs at our institution.…”
mentioning
confidence: 99%